Operation of a Cryogenic Rocket Engine An Outline with Down-to-Earth and Up-to-Space Remarks - Kitsche, Wolfgang. (Springer Aerospace Technology,, 2011)
This book presents the operational aspects of the rocket engine on a test facility. It will be useful to engineers and scientists who are in touch with the test facility. To aerospace students it shall provide an insight of the job on the test facility. And to interested readers it shall provide an impression of this thrilling area of aerospace.